Reconstruction of Zakat in the Digital Era: An Analysis Using Double-Movement Approach - Moh Shadam Taqiyyuddin Azka; Moh. Alfarizi Putra; Muhammad Nailul Ma'arif (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2026)
The development of digital technology has transformed zakat payment practices through the use of various digital financial platforms. This study aims to examine the legitimacy of digital zakat through Fazlur Rahman’s Double Movement hermeneutical approach by exploring the moral ideals embedded in Qur’anic verses on zakat and their relevance to the development of the digital economy. This research employs a qualitative approach using library research. The data were collected from Qur’anic verses related to zakat, classical and contemporary tafsir works, fiqh literature, and previous studies on digital zakat. Data analysis was conducted using the Double Movement theory through two stages: reconstructing the historical context of the revelation of zakat verses and contextualizing their universal values within the realities of the digital economy. The findings indicate that the primary objectives of zakat are the equitable distribution of wealth, the purification of wealth and the soul, and the strengthening of social solidarity. Therefore, the legitimacy of zakat payment is not determined by the form of the payment medium, but rather by the fulfillment of Sharia principles, including lawful ownership, measurable asset value, and the proper delivery of zakat to eligible beneficiaries (mustahiq). These findings reinforce the relevance of the Double Movement theory in bridging the normative teachings of the Qur’an with the development of the digital economy while providing a normative foundation for the advancement of digital zakat services in Indonesia.